IDENTIFIKASI PENYEBAB PENYAKIT BULAI PADA TANAMAN JAGUNG DI SULAWESI SELATAN MENGGUNAKAN PENDEKATAN POLYMERASE CHAIN REACTION - Adriati Thamrin; Herman Herman; Zulfitriany D. Mustaka; Helda Ibrahim (Percetakan Umi Toaha Makassar, 2026)
Downy mildew remains one of the major constraints in maize production in South Sulawesi and is commonly diagnosed based on visual symptoms in the field. This study aimed to identify the causal agent of downy mildew in maize using a molecular approach based on Polymerase Chain Reaction (PCR). Leaf samples showing downy mildew-like symptoms were collected from nine major maize-producing districts in South Sulawesi, namely Gowa, Jeneponto, Bone, Sidrap, Pinrang, Wajo, Enrekang, Sinjai, and Soppeng. Pathogen detection was performed using specific primers PpUF and PpUR targeting Peronosclerospora spp. The PCR results revealed that Peronosclerospora spp. was positively detected in most sampling locations, particularly in Gowa, Jeneponto, Bone, Sidrap, Pinrang, Wajo, Enrekang, and Soppeng. In contrast, samples from Sinjai showed negative PCR results despite exhibiting visual symptoms resembling downy mildew. These findings indicate that field symptoms do not always correspond to the actual presence of Peronosclerospora spp. at the molecular level. This study highlights the importance of molecular-based diagnosis in improving the accuracy of downy mildew identification and provides a scientific basis for more precise and evidence-based disease management strategies in maize cultivation.